PENINGKATAN HASIL BELAJAR SISWA ASPEK KOGNITIF DAN PSIKOMOTORIK DALAM MEMBUAT SKETSA DAN PETA WILAYAH YANG MENGGAMBARKAN OBJEK GEOGRAFI MELALUI METODE SURVEI LAPANGAN - Woro Kristiningtyas (Universitas Muria Kudus, 2017)
This study aims to increase student learning of cognitive and psychomotor aspects in making sketches and maps of the area that describes the object of geography in class VII B SMP N 2 Jakenan. The research was conducted inside and outside the classroom to conduct a field survey around the school and village offices Glonggong. The research subject is class VIIB conducted with two cycle cycles, each cycle consisting of planning, acting, observing and reflecting. The research proves that the application of a field survey methods can improve student learning outcomes on cognitive aspects with an average grade of 53.32 - 69.19 to 78.55; psychomotor aspect was no increase in the average grade of 58.00 to 70.81 - 79.52 with indicators increase students' ability to collect data, geography placing objects in the image, complete the elements of sketches and maps of the area and were able to finish the sketches and maps of the area the aesthetic value according to the rules cartographical correct. It is concluded that the cognitive aspects of student learning outcomes and psychomotor aspects can be improved through a field survey methods.